(untitled) (Dhaka University Journal of Science, 2022)
Objective of this study is to analysis the MHD flow over a curved stretching surface. In this model we incorporated the radiation, mixed convection and partial slip parameter. Using a curvilinear coordinate system developed a mathematical model and the system of basic governing equations are converted into ordinary differential equations with appropriate transformations. The obtained results are solved by using bvp4c solver. The numerical; results for the velocity and temperature as well as the physical quantities such as skin friction and rate of heat transfer are determined and discussed through graph. Results shown that the velocity and temperature decreases with increasing values of curvature parameter and but for magnetic parameter velocity decreases whereas temperature profile increase. Comparison with previous literature are also shown in tabular form and found excellent agreement. Dhaka Univ. J. Sci. 69(3): 171-178, 2022 (June)